ANALISIS DAMPAK PERISTIWA PENGUMUMAN PERINGKAT SUKUK TERHADAP REAKSI PASAR PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - Imran, Fadila; Fitri, Meutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this research is to analyze the impact of sukuk rating announcement event upon market reaction in company which registered at Jakarta Islamic Index (JII) from 2011 until 2015 using average abnormal return during five days before and after event. The type of data used in this research is secondary data which obtained from financial statements publishing by capital market reference center that existed in Indonesia Stock Exchange. The sample used in this research is study case with the total of the population is 7 companies. Method used in this research is purposive sampling which yielded 5 companies sample for sukuk rating announcement event. Meanwhile, the examination of hypothesis used is event study method. The result of this research illustrate that sukuk rating announcement event did not give an impact upon market reaction. However, in case of considering each variable, there is a difference between before and after the occurrence of sukuk rating announcement event.